2017
DOI: 10.18203/2394-6040.ijcmph20170741
|View full text |Cite
|
Sign up to set email alerts
|

The correlation of obesity, smoking, fried foods consumption pattern and food intake with lipid profile in civil servant in Yogyakarta, Indonesia

Abstract: Background: Dyslipidemia is an abnormal change in the levels of lipid profile such as increased levels of total cholesterol, LDL, triglycerides or decreased levels of HDL. The proportion of the Indonesian population (> 15 years old) with a total cholesterol level above the normal value amounted to 35,9%.  Objective: To determine the correlation of obesity, smoking, fried food consumption pattern and food intake with lipid profile in civil servant in Yogyakarta.Methods: This study is an observational study w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 6 publications
1
9
0
1
Order By: Relevance
“…This is because most of the respondents are female and do not smoke, while only a small proportion of smokers are male. This study is in line with research (Sudargo, et al, 2017) which also showed that there was no significant relationship between smoking and hypercholesterolemia.…”
Section: Relationship Between Bmi and Hypercholesterolemiasupporting
confidence: 92%
See 3 more Smart Citations
“…This is because most of the respondents are female and do not smoke, while only a small proportion of smokers are male. This study is in line with research (Sudargo, et al, 2017) which also showed that there was no significant relationship between smoking and hypercholesterolemia.…”
Section: Relationship Between Bmi and Hypercholesterolemiasupporting
confidence: 92%
“…People who are obese or overweight can increase cholesterol levels. A person who is overweight has higher levels of total cholesterol, LDL, and triglycerides compared to normal body weight (Sudargo, et al, 2017). The prevalence of hypercholesterolemia was higher in individuals with overweight/obese versus normal BMI (Subhan & Chan, 2019).…”
Section: Relationship Between Bmi and Hypercholesterolemiamentioning
confidence: 93%
See 2 more Smart Citations
“…Based on the National Health Survey 2013, West Java is one of the five provinces with the highest consumption of fat and cholesterol and also fried food above the national average. Finding reported that individual consuming fried food which containing trans fatty acid has a higher risk of lipid profile abnormality, which was likely associated with obesity [27,28]. A high-fat diet also is one of the main causes of the development of obesity.…”
Section: Suhartatik and Sartikamentioning
confidence: 99%